Development of a laboratory scale air plasma torch and its application to electronic waste treatment - N. Tippayawong (2018)
Expansion in electrical and electronic equipment trade has led to significant increase in electronic waste which should be dealt with special priority due to its potential negative impact to the public health and the environment. Thermal plasma technology offers a very promising alternative of hazardous waste treatment for the near future. In this study, a laboratory scale apparatus for generating high temperature plasma flame was presented. Design of a 20 kW plasma torch system was based on a non transferred direct current arc discharge with air as a medium gas. In this investigation, measurements of temperature distribution were performed. It was shown that high temperature flames can be generated, comparable to those reported in the literature. The gas temperature was found to increase with an increase in power input. The flame temperature was found to further increase from 1210 K to 1480 K when a small amount of added fuel gas. Assessment of electronic waste treatment using the air plasma system in a batch operation was also carried out. It was shown that the system was able to convert the electronic waste into combustible gas and inert solid residues. High mass loss rate of bulk electronic waste was demonstrated. © IRSEN, CEERS, IAU.